Progress in Agrobacterium-mediated transformation of cassava (Manihot esculenta Crantz) - Sarria, Rodrigo A.; Balcázar, N; Destéfano Beltrán, L.J.C.; Roca, W. (International Center for Tropical Agriculture, 1995)
To help solve breeding problems in cassava that have long eluded conventional strategies, a routine transformation protocol is esential. The agropine-mannopine nondisarmed strain of Agrobacterium tumefaciens (CIAT 1182) was selected and used with the binary vector pGV1040. This vector contains the npt II, gus, and bar genes. Inoculations were carried out on cotyledonary leaves obtained from somatic embryos of cassava cultivar M Peru 1983. Following co-cultivation, somatic embryos were induced in a selection medium, supplemented with 16-32 mg/l of Basta. Several Basta-resistant plantlets were obtained. Positive lines were screened, using the polymerase chain reaction (PCR), together with specific primers for the gus and products analyzed on Southern blots under highly stringent conditions. Only lines showing the presence of both genes were transplanted to pots. Genomic Southern analysis of these plants are new under way